The Effect of Promotion, Online Customer Reviews, and Perceptions of Ease of Use on Purchase Decisions at the Tiktok Shop in Denpasar - Putu Indah Hapsari; I Ketut Johny Pramanda Putra; Kartika Kusumawardani (PT Keberlanjutan Strategis Indonesia, 2026)
The problem formulation in this study is how the influence of promotions, online customer reviews and perceived ease of use on purchasing decisions at TikTok Shop in Denpasar. The purpose of this study is to determine the influence of promotions, online customer reviews and perceived ease of use on purchasing decisions at TikTok Shop in Denpasar. The population in this study were all consumers who use TikTok Shop in Denpasar City who have made purchases at TikTok Shop, the number of which is not known for certain. The sample in this study amounted to 200 respondents taken using the purposive sampling method. The research method used is a quantitative method. Technical data analysis uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, Coefficient of Determination Test (R2) and F Test using SPSS version 30. The results obtained in this study are partially the variables of promotion, online customer reviews and perceived ease of use have a positive and significant effect on purchasing decisions. Simultaneously the variables of promotion, online customer reviews and perceived ease of use have a positive and significant effect on purchasing decisions.